2004
DOI: 10.1111/j.1365-2265.2004.02121.x
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin secretion is inhibited by glucose load and insulin‐induced hypoglycaemia but unaffected by glucagon and arginine in humans

Abstract: Ghrelin secretion in humans is inhibited by OGTT-induced hyperglycaemia and ITT but not by glucagon and arginine, two substances able to increase insulin and glucose levels. These findings question the assumption that glucose and insulin directly regulate ghrelin secretion. On the other hand, ghrelin secretion is not associated with the GH response to ITT or arginine, indicating that the somatotroph response to these stimuli is unlikely to be mediated by ghrelin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
2
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 65 publications
5
52
2
8
Order By: Relevance
“…In fact, oral or i.v. administration of glucose has been shown to reduce plasma ghrelin concentrations (Ariyasu et al 2002, McCowen et al 2002, Shiiya et al 2002, Nakai et al 2003, Williams et al 2003, Broglio et al 2004. Consistent with these in vivo studies, in the present study, we found that low glucose induced [Ca 2C ] i increase and ghrelin secretion in MGN3-1 cells, whereas high glucose did not.…”
Section: Discussionsupporting
confidence: 82%
“…In fact, oral or i.v. administration of glucose has been shown to reduce plasma ghrelin concentrations (Ariyasu et al 2002, McCowen et al 2002, Shiiya et al 2002, Nakai et al 2003, Williams et al 2003, Broglio et al 2004. Consistent with these in vivo studies, in the present study, we found that low glucose induced [Ca 2C ] i increase and ghrelin secretion in MGN3-1 cells, whereas high glucose did not.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, ghrelin is unlikely to play a major role in the control of corticotroph function since long-term treatment with synthetic GHS causes no significant increase in 24-h cortisol values (25). Moreover, the lack of any association between cortisol and ghrelin secretion during hypoglycaemia had already been reported (26,27). The fact that ghrelin does not mediate the GH and cortisol response to glucagon is also confirmed by our study that demonstrates a clear suppression of circulating ghrelin after i.m.…”
Section: Discussionsupporting
confidence: 74%
“…The protocol was registered at Clinicaltrials.gov (ID NCT01919788). Nine healthy men averagely aged 22.5 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) years with an average BMI of 23.4 (21.7-26.0) kg/m 2 were recruited in this study. All had a normal physical examination.…”
Section: Methodsmentioning
confidence: 99%